Pengaruh modal manusia terhadap orientasi pasar dan kinerja UMKM - Ina Syarifah; Muhammad Kholid Mawardi; Mohammad Iqbal (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This study focused on Songkok Micro Small and Medium Enterprises (MSME) in Gresik Regency, to examine the effect of human capital on market orientation, effect of human capital on performance MSME, and effect of merket orientation on performance MSME. This study processed primary data obtained using a questionnaire distributed to 163 MSME. The research sample was selected using probability sampling method. This study uses a cluster sampling method involving 163 respondents and uses PLS (Partial Least Square) analysis tools with SmartPLS 3.0 software. The results showed that human capital affect market orientation, human capital affect performance MSME, dan market orientation affect performance MSME.